The Pros and Cons of Using Oat in a Gluten-Free Diet for Celiac Patients - Hoffmanová, Iva (Nutrients, 2019)
A therapeutic gluten-free diet often has nutritional limitations. Nutritional qualities such as high protein content, the presence of biologically active and beneficial substances (fiber, beta-glucans, polyunsaturated fatty acids, essential amino acids, antioxidants, vitamins, and minerals), and tolerance by the majority of celiac patients make oat popular for use in gluten-free diet. The health risk of long-time consumption of oat by celiac patients is a matter of debate. The introduction of oat into the diet is only recommended for celiac patients in remission. Furthermore, not every variety of oat is also appropriate for a gluten-free diet. The risk of sensitization and an adverse immunologically mediated reaction is a real threat in some celiac patients. Several unsolved issues still exist which include the following: (1) determination of the susceptibility markers for the subgroup of celiac patients who are at risk because they do not tolerate dietary oat, (2) identification of suitable varieties of oat and estimating the safe dose of oat for the diet, and (3) optimization of methods for detecting the gliadin contamination in raw oat used in a gluten-free diet.